Vascular endothelial growth factor and hypoxia-inducible factor-1α gene polymorphisms and coronary collateral formation in patients with coronary chronic total occlusions. (22nd June 2016) - Amoah, Vincent; Wrigley, Benjamin; Holroyd, Eric; Smallwood, Andrew; Armesilla, Angel L; Nevill, Alan; Cotton, James
Introduction: We evaluated the association between two single nucleotide polymorphisms of the vascular endothelial growth factor gene and one of the hypoxia-inducible factor-1α gene and the degree of coronary collateral formation in patients with a coronary chronic total occlusion. Methods: Totally, 98 patients with symptomatic coronary artery disease and a chronic total occlusion observed during coronary angiography were recruited. Genotyping of two vascular endothelial growth factor promoter single nucleotide polymorphisms (−152G>A and −165C>T) and the C1772T single nucleotide polymorphism of hypoxia-inducible factor-1α were performed using polymerase chain reaction and restriction fragment length polymorphism analysis. The presence and extent of collateral vessel filling was scored by blinded observers using the Rentrop grade. Results: We found no association between the vascular endothelial growth factor −152G>A, −165C>T and hypoxia-inducible factor-1α −1772C>T with the presence and filling of coronary collateral vessels. A history of percutaneous coronary intervention and transient ischaemic attack/cerebrovascular accident were associated with the presence of enhanced collateral vessel formation following binary logistic regression analysis. Conclusion: The study findings suggest that coronary collateral formation is not associated with the tested polymorphic variants of vascular endothelial growth factor and hypoxia-inducible factor-1α in patients with symptomatic coronary artery disease and the presence of a chronic total occlusion.